2006
DOI: 10.1007/s10237-006-0041-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of finite compressive strain on chondrocyte viability in statically loaded bovine articular cartilage

Abstract: Recent studies have reported that certain regimes of compressive loading of articular cartilage result in increased cell death in the superficial tangential zone (STZ). The objectives of this study were (1) to test the prevalent hypothesis that preferential cell death in the STZ results from excessive compressive strain in that zone, relative to the middle and deep zones, by determining whether cell death correlates with the magnitude of compressive strain and (2) to test the corollary hypothesis that the viab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…This is likely due to excessive static compression of the cartilage tissue in the transverse direction leading to chondrocyte death. 30 The progression and rate of chondrocyte death can be studied in the future using TUNEL staining and will be a concern in determining the proper scaffold size for different defect sizes. The Ø5.0-mm scaffold demonstrated an interfacial strength that was in between that of the 4-and 6-mm-diameter scaffolds at time zero, but the interface was reinforced with time due to the inward migration of chondrocytes that resulted in a 10-fold increase in interface strength after 42 + days.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to excessive static compression of the cartilage tissue in the transverse direction leading to chondrocyte death. 30 The progression and rate of chondrocyte death can be studied in the future using TUNEL staining and will be a concern in determining the proper scaffold size for different defect sizes. The Ø5.0-mm scaffold demonstrated an interfacial strength that was in between that of the 4-and 6-mm-diameter scaffolds at time zero, but the interface was reinforced with time due to the inward migration of chondrocytes that resulted in a 10-fold increase in interface strength after 42 + days.…”
Section: Discussionmentioning
confidence: 99%
“…They report that immature cartilage exhibits significantly greater amount of cell death compared to mature cartilage, which they attribute to the lower compressive modulus of the immature cartilage in the superficial zone. In a complementary study, Chahine et al (2006) test and reject the hypothesis that cell death in the superficial zone of immature bovine cartilage correlates with the depth-varying strain distribution under static loading; they present results which suggest instead that superficial zone chondrocytes are more vulnerable to prolonged static loading than their middle and deep zone counterparts. Baars et al (2006) explore treatment modalities to help reduce chondrocyte death following injurious loading.…”
mentioning
confidence: 92%
“…The relative fractions of these components and the predominant orientation of the collagen fibrils vary over the tissue depth. Experiments have shown that as a result, the mechanical behaviour of healthy adult articular cartilage is depth-dependent (Buckley et al 2008;Chahine et al 2007;Chen et al 2001a;Choi et al 2007;Erne et al 2005;Guilak et al 1995;Gründer 2006;Laasanen et al 2003;Schinagl et al 1997;Wong et al 1997;Zheng et al 2005). The equilibrium stiffness of AC increases with increasing distance from the articular surface and this is linked to increasing osmotic pressures with increasing distance from the surface (e.g.…”
Section: Introductionmentioning
confidence: 99%